Implementation of the Ecosystem Approach to Fisheries in the North-East Atlantic. A case study of how the Joint Norwegian-Russian Fishery Commission has worked with the EAF - Voronova, Olga (UiT The Arctic University of Norway, 2015)
The Ecosystem Approach in Fisheries became a worldwide trend. More and more countries are adopting and developing this in management framework with different rate of success. There is a widespread agreement about the necessity of a new fisheries management strategy, which is taking into account food web linkages and human activity, which may affect sustainability of ecosystem. However, there is no precise instructions for implementation of the regime. Therefore, the main issue for fisheries managing authorities is to transfer the general guidelines into specific tools for managing resources, The North-East Atlantic always has been productive area, and well established management system. The Norwegian-Russian Commission has long-lasting history of successful cooperation. This case-study investigate, how it will function within ecosystem framework, and how implementation process changing well-established management framework.